PENGARUH KOMUNIKASI DALAM MENCIPTAKAN KEGIATAN BELAJAR MENGAJAR YANG AKTIF - Suci Dharma Putri (ADISAM PUBLISHER, 2024)
Good communication is essential for reducing the probability of miscommunication in teaching and learning activities. This may assist the learner examine his knowledge of right and wrong and become accustomed to expressing opinions, and ideas. The purpose of the author's scientific paper is to provide educators with further knowledge or understanding to enhance their communication skills and establish an engaging learning environment in the classroom. A dynamic classroom conversation can provide a welcoming environment for students to feel at ease and comfortable sharing their thoughts and opinions, which may help them in understanding the subject matter being taught. Furthermore, the author hopes that by exchanging ideas, educators will recognise the value of communication skills in designing engaging teaching and learning activities